Antibacterial potential of four herbal plants (Syzygium cumini, Piper ornatum, Anredera cordifolia, and Alpinia galangan) against Staphylococcus aureus and Escherichia coli - Helmin Elyani; Rio Risandiansyah (JIMR - Journal of Islamic Medicine Research, 2017)
ABSTRACTIntroduction: The lack of new antibiotics and the increasing rate of resistance on pathogens requires the discovery of bioactive compounds with antibacterial activity. Using etnopharmacology knowledge, several Indonesian herbs, in particular Juwet (Syzygium cumini), Sirih merah (Piper ornatum), Binahong (Anredera cordifolia) and Laos (Alpinia galangan) had been shown possess wound-healing, anti-inflammatory and gastroprotective activities. It was postulated that these plants would also have antibacterial activity. Method: This study aims to assess the potential for antibacterial activity of these plants, in which decoctation, methanolic and choloroform extraction was used against Staphylococcus aureus and Escherichia coli growth by measuring and comparing zone of inhibition (ZOI), minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC). Results: All plants tested had some activity against S. aureus, but none were found to be active against E. coli. Furthermore, various extraction methods of S. cumini and A. galangan had antibacterial activity against S. aureus with a ZOI of 10 15 mm and 12 25 mm, respectively, with increased antibacterial activity found in non-polar extracts. Methanolic extract of S. cumini acts as a bactericidal at 0.391 mg/ml, whilst other extracts had a bactericidal activity at 6.25 mg/ml.Conclusion: From four plants tested, methanolic extracts of S. cumini and A. galangan has medium to strong antibacterial activity against clinical S. aureus strains.Keywords: Juwet, Sirih Merah, Binahong, Laos, Antibacterial, Antibiotic